PEMBERDAYAAN MASYARAKAT DESA SIDOHARJO DALAM MEWUJUDKAN RUMAH LITERASI BERBASIS KOMUNITAS - Hanifah Noviandari (Asosiasi Dosen Perguruan Tinggi Islam, 2026)
The low interest in reading in the community is influenced by limited access, the lack of non-functional literacy facilities, the lack of literacy community, and the lack of collective awareness of the importance of reading culture. This community service was carried out with the aim of identifying and developing the local potential of the people of Sidoharjo Village in supporting the establishment of the Literacy House as a center for community-based literacy activities. To achieve this goal, this service is carried out through an innovation seminar on Literacy House Management to Develop Reading Culture in the Digital Era. This method of service uses Asset-Based Community Development (ABCD). The service was carried out for 3 months. The target participants who will be directly involved are around 30 people. This activity stage reflects the five main steps of the ABCD approach, namely discover, dream, design, define, and destiny/deliver. The results of the implementation show that the program is able to increase knowledge, awareness, and active involvement of the community on the importance of literacy in the context of digital technology development. The seminar focused on increasing participants' understanding of the concept of digital literacy, strategies for strengthening reading culture, and the role of Literacy House as a community learning center. Through these activities, a village literacy driving team was formed, there was an increase in community participation in reading and writing activities, and productive collaboration was established between the community, village government, educational institutions, and local entrepreneur.